Litigation and Students With Disabilities: An Overview of Cases From 2015. (March 2016) - Katsiyannis, Antonis; Counts, Jennifer; Popham, Michelle; Ryan, Joseph; Butzer, Madeline
Special education is the most highly litigated area within the field of education. Therefore, the purpose of the current article is to highlight cases (court decisions, Office of Civil Rights rulings, and State Educational Agency hearings) involving students with disabilities in 2015. Highlights from the case law point to the need for school districts to ensure that students with disabilities are provided free appropriate public education, ensure timely and comprehensive evaluations once a suspected disability is of concern, ensure that students with autism have access to an range of services, provide evidence in factors considered when determining placement, remove students only when they present imminent threat to self or others, and appropriately address bullying/harassment instances.